Business Judgment Rule as Legal Protection for Directors in Non-Performing Loan Cases at Indonesian State-Owned Banks - Umar Iskandar; M. Ersyad Indra; Darniaty Azis (CV. Era Digital Nusantara, 2026)
The implementation of the Business Judgment Rule (BJR) in Indonesian State-Owned Enterprise (SOE) banking remains a significant legal issue due to the overlap between corporate law and anti-corruption law. Business decisions resulting in Non-Performing Loans (NPLs) are frequently interpreted as state financial losses, creating legal uncertainty and exposing directors to criminal liability despite acting in good faith. This study aims to examine the criminal liability of SOE bank directors in credit decision-making and to evaluate the effectiveness of the Business Judgment Rule in distinguishing legitimate business risks from criminal conduct. This research employs a normative legal (doctrinal) approach using statutory, comparative, and case study approaches. Primary legal materials include the Anti-Corruption Law, the Limited Liability Company Law, Law No. 1 of 2025 on State-Owned Enterprises, Financial Services Authority regulations, and relevant Constitutional Court and Supreme Court decisions. The findings indicate that the Business Judgment Rule has a strong legal foundation under Article 97 of the Limited Liability Company Law, Law No. 1 of 2025 on SOEs, and Constitutional Court Decision No. 62/PUU-IX/2013, which recognizes the separation of SOE assets from state assets. However, its implementation remains constrained by inconsistent judicial interpretation and the expansive application of anti-corruption provisions. Comparative analysis with the United States demonstrates that explicit recognition of BJR as a safe harbor provides greater legal certainty for corporate directors. Therefore, harmonization between corporate and criminal law, together with the explicit codification of the Business Judgment Rule within Indonesia’s anti-corruption legal framework, is essential to strengthen legal certainty, protect directors acting in good faith, and promote sound corporate governance in State-Owned Enterprises.